LKPD Discussion Activity Terintegrasi Keislaman dengan Pendekatan Pictorial Riddle pada Materi Pecahan - Rizkiah, Alin Wahyu; Nasir, Nasir; Komarudin, Komarudin (Universitas Islam Negeri Raden Intan Lampung, 2018)
This study aims to develop and to determine the response of teachers and learners to LKPD discussion activity that integrates Islamic values with a pictorial riddle approach on the fractional subject, based on the modification of development proposed by Sugiyono. Data analysis techniques used are qualitative and quantitative data analysis techniques. Result of research of development of LKPD with stage which is done that consist of 7 stages: (1) potential and problem; (2) data collection; (3) product design; (4) product validation; (5) product revisions; (6) product trial and (7) product revision. Validation is done by material experts, media experts, and religious experts. Product trials were conducted in 2 phases: small group trials and field trials. The validation results obtained from the material experts that the product developed has reached the criteria both in the aspect of quality content, an accuracy of coverage, pictorial riddle approach, and language. Validation of media experts stated in the aspect of size, skin design, and content design on LKPD reach good criteria. The validation of Islamic scholars on the quality aspects of the content, the language aspect, and the material emphases attributed to the criteria are very good, so the product is declared worthy of use. Students' responses in small group trials obtained a mean of 91.67 with very interesting criteria and field trials obtained an average score of 87.67 with very interesting criteria, test responses were also made to teachers with an average score of 89, 6 with very interesting criteria.